Diagnosis of Human Visceral Pentastomiasis - Tappe, Dennis (Public Library of Science, 2009)
Visceral pentastomiasis in humans is caused by the larval stages (nymphs) of the arthropod-related tongue worms Linguatula serrata, Armillifer armillatus, A. moniliformis, A. grandis, and Porocephalus crotali. The majority of cases has been reported from Africa, Malaysia, and the Middle East, where visceral pentastomiasis may be an incidental finding in autopsies, and less often from China and Latin America. In Europe and North America, the disease is only rarely encountered in immigrants and long-term travelers, and the parasitic lesions may be confused with malignancies, leading to a delay in the correct diagnosis. Since clinical symptoms are variable and serological tests are not readily available, the diagnosis often relies on histopathological examinations. This laboratory symposium focuses on the diagnosis of this unusual parasitic disease and presents its risk factors and epidemiology.